Teaching sport concepts and skills a tactical games approach for ages 7 to 18 - Mitchell, Stephen A.; Oslin, Judith L.; Griffin, Linda L. (Human Kinetics, 2013)
The third edition of the popular book Teaching Sport Concepts and Skills : A Tactical Games Approach for Ages 7 to 18 now covers the elementary level as well as middle and secondary levels. It shows teachers how to move from a traditional to a tactical games teaching approach with detailed unit and lesson plans, a DVD-ROM with video clips and reproducibles, and a standards-linked Game Performance Assessment Instrument (GPAI). ... Focusing on tactical awareness helps students develop problem-solving skills through game play. The tactical approach also allows teachers to individualize instruction for novice, developing, and advanced performers by either reducing or increasing the challenge of the tasks involved. The third edition of Teaching Sport Concepts and Skills will help current and future teachers structure positive and engaging learning experiences that set the stage for improved performance and lifelong enjoyment of sport.